Evaluation of Evidence in Electronic Criminal Case Trials - Esti Aryani; Triwanto (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to study the validity of evidence and evidence in the electronic trial. One of the stages in the examination of criminal cases is proof. Proof is a problem that plays a role in the examination process at a court hearing, because through the evidence of the defendant's fate is determined. Assessment of the validity of the evidence and evidence in the electronic trial must still be in accordance with the provisions of the legislation. This study uses secondary data in the form of laws and regulations, literature books related to research material. The data obtained was then analyzed using a qualitative analysis method presented in the form of description. The results of the study found that the existing laws and regulations were not sufficient because there were no detailed provisions regarding the validity of both physical and electronic evidence used in electronic trials. Criminal procedural law reforms need to be carried out in order to be a standard guideline for the implementation of electronic trials.